1990
DOI: 10.1128/aem.56.4.1059-1066.1990
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of Salmonella spp. in estuaries by using a DNA probe

Abstract: A method for direct detection of Salmonella spp. in water was developed by using a commercially available DNA probe. Particulate DNA was extracted from 500to 1,500-mi water samples collected from New York Harbor and Chesapeake Bay and used as a substrate for a salmonella-specific DNA probe in dot blot assays. The method detected salmonellae in water samples from 12 of 16 sites, including 6 sites where salmonellae could not be cultured. The specificity of the probe was evaluated, and cross-hybridization, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 31 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…In this study, we found that real-time PCR detection sensitivity from natural samples was higher than bacteriology both in intestinal samples and in total, when the samples taken from each¯ock were considered individually (Table 1). Possible reasons for this can be as follows: salmonellae found in natural samples may show atypical biochemical pro®les and may not be detected in bacteriology (Bennet et al 1998), and Salmonella cells may be present in a viable but non-culturable status (Knight et al 1990). The number of Salmonella-positive¯ocks was 13 (27á7%) both by PCR and culture method.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that real-time PCR detection sensitivity from natural samples was higher than bacteriology both in intestinal samples and in total, when the samples taken from each¯ock were considered individually (Table 1). Possible reasons for this can be as follows: salmonellae found in natural samples may show atypical biochemical pro®les and may not be detected in bacteriology (Bennet et al 1998), and Salmonella cells may be present in a viable but non-culturable status (Knight et al 1990). The number of Salmonella-positive¯ocks was 13 (27á7%) both by PCR and culture method.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the number of positive individual samples by real-time PCR was almost double that detected by the culture method. A possible explanation of these results is that salmonellae found in natural samples may show atypical biochemical profiles and may not be detected using bacteriological methods, and that Salmonella cells may be present in a viable but nonculturable state (Knight et al 1990;Bennett et al 1998;Eyigor et al 2002). In recent years, several studies have been published in which the use of a conventional PCR assay proved more sensitive than the culture method for detecting Salmonella in poultry, meat, and poultry-related products (Bennett et al 1998;Whyte et al 2002;Oliveira et al 2002;Fratamico 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although the DNA-DNA hybridization method using Salmonella-specific DNA probes offers one of the rapid methods for Salmonella detection (Fitts et ul. 1983;Tsen et al 1989Tsen et al , 1991Knight et al 1990;Cano et al 1992), this method requires enrichment steps for target cells and thus, about 48-72 h are needed to complete the detection (Emswiler-Rose et al 1987;Tsen et al 1991). The polymerase chain reaction (PCR) technique offers another possibility for rapid detection of Salmonella.…”
Section: Introductionmentioning
confidence: 99%
“…Although 23s rRNA targeted DNA probes have been developed (Ronner and Stackebrandt 1994) and are commercially available (Knight et al 1990;Wilson et al 1990b), to our knowledge, 16s RNA gene-based PCR primers have not been developed for the specific detection of Salmonella in foods. Recently, a rapid method for the detection of Salmonella strains using a combination of PCR and reverse dot-blot hybridization has been reported (Iida et al 1993).…”
Section: Introductionmentioning
confidence: 99%